Stress among nurses from countries variously affected by the COVID-19 pandemic – results collected in Poland and Iran - Andrzej Piotrowski (Nofer Institute of Occupational Medicine, 2021)
Background Nursing involves numerous stressful situations, such as overwork, night shifts, responsibility for the patients’ health, rapid pace of work, emotional demands, contact with suffering individuals, and patients’ aggressive behaviors. The SARS-CoV-2 pandemic is an additional demand on the already demanding profession. Thus, the aim of the current study was to assess the character of the relationship between overwork and subjectively experienced stress, taking into account the moderating role of contact with patients and work in facilities dedicated for COVID-19 patients, and the strategies of coping with stress, including resilience, in countries affected by the pandemic to various degrees.